Analysis of dual-frequency solution method for single-frequency precise point positioning based on SEID model for GPS and BDS. (April 2021) - Hong, Ju; Tu, Rui; Zhang, Rui; Fan, Lihong; Han, Junqiang; Zhang, Pengfei; Lu, Xiaochun
Highlights: The SEID model is used to efficiently correct the ionospheric delay of single frequency stations. The SEID model to BDS-2 and BDS-3 new signals single frequency PPP are evaluated. The performance between single- and dual-frequency PPP is compared for GPS and BDS. Abstract: The Satellite-specific Epoch-differenced Ionospheric delay (SEID) model can effectively correct ionospheric errors, which is of great significance in the application of entailing low-cost global positioning system (GPS) single-frequency (SF) receivers for retrieving tropospheric delays and deformation monitoring. This study aims to explore the impact of the SEID model on SF and dual-frequency (DF) precise point positioning (PPP) based on the GPS–, BeiDou Navigation Satellite System (BDS) –only and the GPS–BDS dual-system. Two sets of data were collected, corresponding to three test networks with DF stations separated by 34, 139, and 172 km, respectively. The GPS, BDS, and GPS–BDS dual-system observations in the networks were utilized to test positioning results, tropospheric delay and the impact of satellite-induced code bias variations existing in BDS on the positioning of DF PPP with ionosphere-free combinations, ionosphere-constrained SF PPP, and SF PPP based on SEID model transformation (STSF). The results show that the positioning results of STSF PPP became slightly inaccurate with increasing reference station separation distances. However, the SF PPP based on the SEID model exhibited substantially improved positioning accuracy and coordinate repeatability of SF PPP especially with regard to BDS, and obtain similar positioning results of DF PPP. The difference in the Standard Deviation (STD) and Root Mean Square (RMS) of the positioning bias of the GPS-only and GPS-BDS dual systems between DF PPP and STSF PPP was similar within 1 cm, but the difference in the case of BDS was as large as 2 cm in the E and U directions in the networks with separations of 139 and 172 km. Furthermore, the improvement of the STD and RMS of the STSF PPP positioning result was the greatest more than 67% for GPS–, BDS–only, and GPS–BDS dual- system in the networks separated by 34 km compared to SF PPP.